A theoretical analysis on self-collapsing of nanotubes. (15th March 2019) - Meng, Xianhong; Zhang, Bowen; Li, Hao; Li, Fengwei; Kang, Zhan; Li, Ming; Chen, Yuli
Abstract: Nanotubes are easy to collapse due to van der Waals interactions and the low bending stiffness of their walls. The collapse may significantly alter the mechanical, thermal, and electronic properties of nanotubes, which can lead to many exciting applications of nanotubes in nanoelectronics and nanocomposites. In this paper, a theoretical model based on finite deformation beam theory is established to analyze the collapsing of single- and multi-wall nanotubes. Using this model, the critical diameters and the profile of collapsed nanotubes are predicted, which agree well with those obtained by molecular dynamics simulations. Furthermore, a simple scaling law of the critical collapse conditions of carbon nanotubes is built as a function of geometrical parameters, which can determine whether the carbon nanotube collapse. This scaling law can be easily extended to determine the collapsing state of other nanotube systems with different bending stiffness and binding energy.